Validity of gymnastics-specific assessment of neuromuscular function of shoulder flexor and extensor muscles to predict performance in gymnastics skills - Milosis, D. C. (The Journal of Strength and Conditioning Research, 2023)
This study examined the relationships between gymnastics-specific laboratory measurements of neuromuscular function of the shoulder flexor and extensor muscles and performance in specific gymnastics skills. Fifteen highly competitive male gymnasts and 18 male students (age 20.41 ± 2.51 years, body mass 69.7 ± 7.07 kg; mean ± SD) participated voluntarily. The electromyogram (EMG) was used to assess muscle activation of 3 flexor and 3 extensor shoulder muscles during isometric (45, 90, and 135°) and isokinetic (concentric and eccentric 60, 180, and 300°/s) flexion-extension of the shoulder. Peak torque (PT), neuromuscular efficiency (NME: torque to EMG ratio), and antagonist coactivation index (CI) were evaluated. Furthermore, performance in specific gymnastics skills was evaluated. The results supported the ecological validity of the measurements. Specifically, significant correlations emerged between the shoulders' neuromuscular function parameters and the performance in the gymnastics skills (PT: r = 0.798, p < 0.001, NME: r = 0.576, p < 0.001, CI: r = -0.351, p < 0.05). In addition, according to the results of the regression analysis, neuromuscular function of the shoulder flexor and extensor muscles predicted gymnastics performance. Specifically, the model that was produced significantly predicted the dependent variable (performance in specific gymnastics skills) in all steps and explained a total variance of 64.4% (p < 0.001). Based on beta coefficients, PT had the higher contribution to the prediction of performance. The insight gained on these relationships could help coaches to plan the training of their gymnasts and to monitor the longitudinal changes in neuromuscular function of shoulder muscles induced by training more effectively.